Mistletoe miracles eaudiobook Ransom canyon series, book 7. - Thomas, Jodi (Ransom Canyon, 2019)
A small-town Texas Christmas story, where hearts are lost, love is found, and family always brings you back home. Griffin Holloway is desperate: the Maverick Ranch has been in his family for generations, but lately, it's a money pit. He'd sooner marry one of his horses than sell the ranch. Marriage, though, could be a solution. If he can woo a wealthy bride, he might save the ranch-just in time for Christmas. Jaxon O'Grady likes his solitude just fine, thank you very much. But when a car accident brings the unexpected to his door, he realizes just how much one person can need another. Crossroads is the perfect place for Jamie Johnson: avoiding nosy questions about why she's single, she's happy to keep to her lakeside home. So she's baffled when she gets the strangest Christmas present of all, in the form of a Mr. Johnson, asleep on her sofa. Who is he, and why does everyone think he's her husband? In this uplifting novel, three unlikely couples discover just what Crossroads, Texas, can offer: romance, belonging, and plenty of Christmas spirit.